Exploring the Potential Asymmetric Structures in the Causal Relationship between Financial Development and Economic Complexity: : Empirical Insights from Nigeria - Olaniyi, Clement Olalekan (Otoritas Jasa Keuangan, 2026)
This study is one of the earliest to examine the potential asymmetry in the causal relationship between financial development (FD) and economic complexity (ECI), using Nigeria’s dataset for the period 1964-2023. Unlike previous studies, which assume impractical linear and symmetric features in the causal analysis between FD and ECI, this study examines the potential asymmetry. The study employs unit root tests (linear and nonlinear), Hatemi-J’s data decomposition procedure, and a leverage-adjusted bootstrap simulation of Hatemi J’s causality test. The findings reveal robust asymmetric structures in both ECI and FD data distribution. The results indicate neither symmetric nor asymmetric causality between ECI and FD. These findings have some profound implications. On the one hand, it shows that neither Nigeria’s financial sector’s expansionary (positive change components) nor contractionary (negative change components) policies are causal drivers of ECI upgrades or deterioration. On the other hand, ECI-related initiatives lack the causal potency to spur the development of Nigeria’s financial sector. The study concludes that evidence of asymmetric causality between ECI and FD depends on context and scope.